Endodontic periapical lesion-induced mental nerve paresthesia - Elham Shadmehr; Neda Shekarchizade (Wolters Kluwer Medknow Publications, 2015)
Paresthesia is a burning or prickling sensation or partial numbness, resulting from neural injury. The symptoms can vary from mild neurosensory dysfunction to total loss of sensation in the innervated area. Only a few cases have described apical periodontitis to be the etiological factor of impaired sensation in the area innervated by the inferior alveolar and mental nerves. The aim of the present paper is to report a case of periapical lesion-induced paresthesia in the innervation area of the mental nerve, which was successfully treated with endodontic retreatment.